PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK DIGITAL BERBASIS QR CARD PADA PEMBELAJARAN IPAS SISWA KELAS IV SDN NGADIREJO - Dewi Andaiyani, Sri; Trisnayanti, Yetty; Lokaria, Eka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a QR Card-based digital comic media design in science learning. Testing the validity, practicality, and effectiveness of QR Card-based digital comic media in science learning for fourth-grade students of SDN Ngadirejo. This type of research is Research and Development with a 4D development model. The subjects of this study are fourth-grade students of SDN Ngadirejo. Data collection techniques use observation, interviews, questionnaires, and tests. Based on the results of the validation analysis of QR Card-based digital comic media in science learning using Aiken’s V, the assessment of the language validator is 0,90 with a high category, the media validator is 0,89 with a high category and the material validator is 0,86 with a high category. Analysis of the assessment of teacher and student practicality sheets shows that QR Card-based digital comic media in science learningmeets the very practical criteria with an average score of 91%. Then the effectiveness assessment analysis obtained an average N-Gain score of 0,76 with a high category. Based on the research results, it can be concluded that QR Card-based digital comic media in science learning is proven to be valid, practical, and affective so that it is suitable for use in the learning process of class IV SDN Ngadirejo.